Students Perception towards the Use of Insert Learning App in Blended Learning to Enhance Reading Comprehension - Ulya, Solihatul; Aprilia, Mercy; Mustofa, Mutmainnah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
One of essential skills to expand students’ knowledge and abilities is reading. Various media and platforms have been used by teachers to support the learning and teaching process moreover during the online class. However, to help students to easily understand about what they read, teachers have to make and provide technique, strategy and media for the needs of their students, including in reading mastery. The use of appropriate media can be pivotal for teachers in order to make the students understand by considering its efficiency. This paper focuses on investigating the students’ perception towards the use of Insert Learning App in Blended Learning and Teaching to enhance students’ comprehension in reading. This study uses a case study method. The participants were master degree students of English Department, in total 50 students consisted of 22 male students and 38 female students. To find out the students’ perception towards the use of Insert Learning, the data were collected mainly through questionnaires and interviews. The result of this study reveals that the majority of students have positive perceptions regarding the usage of Insert Learning as a teaching media for reading comprehension in blended learning. It is beneficial tools to makes reading more interactive and engaging. Students also claim that Insert Learning is easy to use because it is connected as an extension in Google Chrome.